Therapeutic community in the public policy of mental health: tensions and divergences (Research, Society and Development, 2020)
Two logics of organization and intervention in the field of mental health for people with problematic involvement of psychoactive substances make up the Brazilian scenario. On the one hand, we have public policies articulated in networks of psychosocial support and connected with the guarantee of human rights, social and community intervention and harm reduction, on the other hand, we have therapeutic communities that support their practices in a tripod of discipline, spirituality and residential assistance regime and abstaining from drug use. Thus, this study aims to develop reflections on the tensions and battles between these two logics. For this, we used the bibliographic research in which a description was made of the history of the therapeutic communities, their articulation and regulation employed in Brazil, how they are organized and, concomitantly, the expansion of their political strength when they are able to enter the Health Unic System (SUS) being recognized as a service in the Psychosocial Care Network (RAPS). The tensions are present in the divergence in the direction of interventions, in the denunciations and defenses made by both fields, the changes employed by the current Brazilian government when financing and resuming asylum practices in mental health policy. These events make us question how the achievements of the Brazilian Psychiatric Reform are being attacked, demanding the organization and defense in this battlefield aiming at the continuation of an anti-asylum struggle.